The influence of modernity on eating behavior: A review (Research, Society and Development, 2021)
The aim of this study was to verify changes in eating behavior influenced by modern life. This is an integrative literature review carried out in the Publisher Medline (PubMed), Science Direct and Web of Science databases with pre-selected descriptors. The results showed that food, commensality and food culture suffer interference in the face of modern life and globalization. There were drastic changes in eating habits and practices, with a tendency to worsen the quality of meals, decreased socialization and sharing of meals among family members, diffusion and fragmentation of food cultures. The act of eating with pleasure can be compromised, due to the rush of daily routine, distance from home, absence of social interaction or lack of food options in the market with which individuals identify themselves with their culture. Furthermore, there is an inclination towards overvaluing the food culture of origin and the attempt to reproduce it, especially when living with different cultures, within which cuisine can be an agent of social exclusion, with the rescue of the culture of origin being a way of reaffirm yourself as an individual. In this context, the prospects are worrying, as an even greater decrease in social interaction during meals is expected.